Advances in Accounting and Finance Management: A Systematic Review of Financial Markets, Risk, and Corporate Practices - Mayank Nagpal (Journal of Advanced Research in Accounting and Finance Management, 2026)
Accounting and finance management play a vital role in supporting organisational performance, investment decisions, and economic development. Over the last two decades, rapid globalisation, technological advancement, and financial market integration have transformed financial management practices. This study presents a systematic review of the literature on accounting and finance management with a particular focus on financial markets, risk management, and corporate practices. The review synthesises scholarly work published in leading journals to identify major research themes, theoretical developments, and emerging trends in the field. The findings highlight the importance of corporate governance, financial reporting quality, financial risk management, and market competition in shaping financial performance. Additionally, the review identifies the growing role of digital technologies, big data analytics, and regulatory frameworks in improving transparency and decision-making in financial systems. The paper concludes by discussing research gaps and suggesting directions for future research in accounting and finance management.